Intermittent hypoxic training at low altitude and its impact on EPO and VEGF - Mikulski, T. (Medicina Sportiva, 2013)
About natural and artificial altitude training and its effects on EPO and VEGF (beneftits, inconveniencies, the perfect solution , intermittent hypoxic training and the application in sport).